Vectorial analysis of the electrocardiogram from conventional limb leads in healthy adult Nepalese females - Prajapati, Rajesh; Amatya, Neebha; Magar, Rajab Rana; Shrestha, Ripti (Journal of Gandaki Medical College-Nepal, 2021)
Introduction: ECG interpretation plays a vital role in the initial evaluation of patients presenting with cardiac complaints. Assessment of degree of cardiac vector is one of the important parameters to be studied in ECG. Methods: A prospective cross-sectional study was carried out among 84 female subjects, aged 18- 40 years of age, including students and staff of Gandaki Medical College Teaching hospital and Research Center, Pokhara, Nepal over a period of one month from 1st Oct to 1st Nov 2021. A Standard ECG machine was used and the ECG was recorded using the conventional limb leads. The individual mean electrical axis of the heart was plotted using the net voltage of QRS complex of Lead-I and Lead-III. The possible correlation between cardiac vector and physical measurements like height weight BSA and BMI were analyzed. The data were analyzed in SPSS version 27. Results: The normal mean electrical axis of the healthy female subjects was observed as 61.7±23.51°. There was a significant positive correlation of cardiac vector with height (p< 0.05), whereas a negative correlation was observed with weight and BMI (p< 0.01). However, there was no significant correlation with BSA. In our study, we observed the maximum left axis cardiac vector as -2° and right axis as 98° among 84 female subjects. Conclusion: Documentation of cardiac vector was made using standard bipolar limb leads in normal healthy female subjects. BMI is involved in the deviation of cardiac vector with a negative correlation. This observation could make it quite attractive for use in clinical practice.